The future of charitable alternative food networks in the UK: an investigation into current challenges and opportunities for foodbanks and community markets - Nayak, Rounaq; Hartwell, Heather (Frontiers in Sustainable Food Systems, 2023)
This study examines the potential of charitable alternative food networks (ANFs), specifically community markets, as a complimentary solution to existing food aid efforts in response to food insecurity. While foodbanks play a crucial role in providing emergency food aid, they often face challenges in terms of supply shortages, limited food variety, and perpetuating dependency on food aid. Moreover, foodbanks may only offer temporary relief without addressing the root cause of food insecurity. Community markets, on the other hand, adopt a social economy approach and aim to empower local communities by providing affordable food options to all community members. These markets operate on a different business model than foodbanks and offer additional vouchers for those who cannot afford to purchase food. Community markets also focus on promoting social and economic goals and often provide additional services and activities within the community centres. By assessing the perspectives of beneficiaries of foodbanks and community markets, the paper examines the dimensions of food security (availability, access, utilisation, and stability) in the context of both charitable AFNs and highlights the potential of community markets and foodbanks to address these dimensions. While there is ongoing debate about categorising food aid programmes as AFNs, both share the goal of reducing food insecurity and promoting sustainable and equitable food systems. Ultimately the paper argues that community markets offer a more sustainable and empowering approach to addressing food insecurity by addressing its underlying causes and promoting community resilience.